2018
DOI: 10.1111/cmi.12817
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium yoelii S4/CelTOS is important for sporozoite gliding motility and cell traversal

Abstract: Gliding motility and cell traversal by the Plasmodium ookinete and sporozoite invasive stages allow penetration of cellular barriers to establish infection of the mosquito vector and mammalian host, respectively. Motility and traversal are not observed in red cell infectious merozoites, and we have previously classified genes that are expressed in sporozoites but not merozoites (S genes) in order to identify proteins involved in these processes. The S4 gene has been described as criticaly involved in Cell Trav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 64 publications
2
12
0
Order By: Relevance
“…Ron2 knockdown decreased the abilities of cell traversal and invasion of hepatocytes and resulted in a reduction in the number of parasites in the liver after intravenous sporozoite inoculation. This phenotype reconciles previous studies demonstrating that mutant sporozoites with less attachment/gliding ability-such as TRAP-like protein (TLP) knockout, POFUT2 knockout, and S4/Celtos knockdown-show decreased cell traversal and/or cell invasion capacity (Lacroix & Ménard, 2008;Lopaticki et al, 2017;Steel et al, 2018). Therefore, it is indicated that decreased infectivity of ron2 knockdown sporozoites to mice is due to the defect in attachment/gliding ability.…”
Section: Contribution Of Ron2 To Sporozoite Transmission To Mammalisupporting
confidence: 87%
See 1 more Smart Citation
“…Ron2 knockdown decreased the abilities of cell traversal and invasion of hepatocytes and resulted in a reduction in the number of parasites in the liver after intravenous sporozoite inoculation. This phenotype reconciles previous studies demonstrating that mutant sporozoites with less attachment/gliding ability-such as TRAP-like protein (TLP) knockout, POFUT2 knockout, and S4/Celtos knockdown-show decreased cell traversal and/or cell invasion capacity (Lacroix & Ménard, 2008;Lopaticki et al, 2017;Steel et al, 2018). Therefore, it is indicated that decreased infectivity of ron2 knockdown sporozoites to mice is due to the defect in attachment/gliding ability.…”
Section: Contribution Of Ron2 To Sporozoite Transmission To Mammalisupporting
confidence: 87%
“…This phenotype reconciles previous studies demonstrating that mutant sporozoites with less attachment/gliding ability-such as TRAP-like protein (TLP) knockout, POFUT2 knockout, and S4/Celtos knockdown-show decreased cell traversal and/or cell invasion capacity (Lacroix & Ménard, 2008;Lopaticki et al, 2017;Steel et al, 2018). Ron2 knockdown decreased the abilities of cell traversal and invasion of hepatocytes and resulted in a reduction in the number of parasites in the liver after intravenous sporozoite inoculation.…”
Section: Contribution Of Ron2 To Sporozoite Transmission To Mammalisupporting
confidence: 87%
“…Strikingly, in the case of both programs, well-characterized mRNAs are regulated to allow production of their encoded proteins when they are required for the parasite’s activities. For instance, the TR-oospz to UIS Protein program (Table 3) controls production of PLP1/PPLP1/SPECT2, CelTOS, and TLP, which are critical or essential for the sporozoite to navigate the host skin, vasculature, and liver 34, 46, 47, 5759 . Analyses of the complete TR-oospz to UIS Protein dataset reveal significant GO terms noting roles in the apical invasion complex, the parasite cell surface, movement in host environments, and interaction with and entry into host cells (Table S6).…”
Section: Resultsmentioning
confidence: 99%
“…P25 and P28 protect the ookinete from the hostile environment of the midgut (Tomas et al, 2001), and along with enolase (Ghosh et al, 2011) and CTRP (circumsporozoite and TRAP-related protein) (Dessens et al, 1999;Yuda et al, 1999) are thought to facilitate initial interactions with the epithelial cell surface. PPL3 (Kadota et al, 2004) and 5 (Plasmodium perforin like proteins 3 and 5) (Kadota et al, 2004;Ecker et al, 2008), PSOP (putative secreted ookinete protein) 2 and 7 (Ecker et al, 2008), and SOAP (secreted ookinete adhesive protein) (Dessens et al, 2003), WARP (von Willebrand factor A domain-related protein) (Yuda et al, 2001), and LIMP (Santos et al, 2017) have functions in invasive motility, while SUB2 (subtilisin-like protease 2) (Han et al, 2000) and CelTOS (cell traversal protein for ookinetes and sporozoites) (Kariu et al, 2006;Steel et al, 2018) have been identified to play a role in traversal of the midgut epithelium and oocyst survival.…”
Section: Introductionmentioning
confidence: 99%